Band Gap Implications on Nano-TiO2 Surface Modification with Ascorbic Acid for Visible Light-Active Polypropylene Coated Photocatalyst - Chiara Anna D’Amato; Rita Giovannetti; Marco Zannotti; Elena Rommozzi; Marco Minicucci; Roberto Gunnella; Andrea Di Cicco (Nanomaterials, 2018)
The effect of surface modification using ascorbic acid as a surface modifier of nano-TiO2 heterogeneous photocatalyst was studied. The preparation of supported photocatalyst was made by a specific paste containing ascorbic acid modified TiO2 nanoparticles used to cover Polypropylene as a support material. The obtained heterogeneous photocatalyst was thoroughly characterized (scanning electron microscope (SEM), RAMAN, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), photoluminescence (PL), and Diffuse Reflectance Spectra (DRS) and successfully applied in the visible light photodegradation of Alizarin Red S in water solutions. In particular, this new supported TiO2 photocatalyst showed a change in the adsorption mechanism of dye with respect to that of only TiO2 due to the surface properties. In addition, an improvement of photocatalytic performances in the visible light photodegration was obtained, showing a strict correlation between efficiency and energy band gap values, evidencing the favorable surface modification of TiO2 nanoparticles.